[Peniguel, Francesca (ballerina/dancer) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Peniguel, Francesca, -- 1979-; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia